ANALYSIS OF POINT CONTACTS SUBJECTED TO A CONCENTRATED NORMAL FORCES - Stefan GHIMIȘI (Fiabilitate şi Durabilitate)
To "non-compliant" contacts in which deformations are sufficiently small compared to the size of bodies, elasticity theory applies to closed contact defined by the contact area. Stresses and displacements in elastic semispaces can cause tractions of the surface, being deducted for the first time by Boussinesq (1885) and Cerruti (1882)